ANALISIS STRATEGI KOMUNIKASI PEMASARAN ECOTOUCH PADA MEDIA SOSIAL INSTAGRAM (@ecotouch_id) - Kristin Agustina (2023)
This research aims to discuss the marketing communication strategies implemented by EcoTouch on the social media platform Instagram (@ecotouch_id) using the concept of Integrated Marketing Communication (IMC) proposed by Belch & Belch. The method employed in this study is descriptive qualitative research using primary and secondary data sources. The sampling technique used is purposive sampling. The researchers analyzed the data using Miles and Huberman's data analysis model or the interactive data analysis method, which includes data collection, data reduction, data presentation, and drawing conclusions/verification through data triangulation. The final results of this research indicate that EcoTouch indeed implements marketing communication strategies on Instagram (@ecotouch_id) in line with the concept of Integrated Marketing Communication. However, there is one marketing communication strategy that is not utilized on Instagram, which is personal selling. Additionally, it was found that EcoTouch actively engages in marketing on Instagram to build brand awareness by educating the public about eco-friendly and sustainable products.